Design and synthesis of a vanadate-based ratiometric fluorescent probe for sequential recognition of Cu2+ ions and biothiols. Issue 24 (30th October 2019) - Zeng, Hui-Hui; Zhou, Zhi-Ying; Liu, Fang; Deng, Jie; Huang, Shu-Yun; Li, Guo-Ping; Lai, Pei-Qing; Xie, Yue-Ping; Xiao, Wei
Abstract : YVO4 :Eu 3+ @CDs core–shell nanomaterial was synthesized through a simple self-assembly of carbon dots (CDs) with YVO4 :Eu 3+, since the high affinity of oxygen-containing groups such as –COOH or –OH of CDs to the metal ions on the surface of YVO4 :Eu 3+ . Abstract : A novel YVO4 :Eu 3+ @CDs core–shell nanomaterial with two main emission peaks at 405 and 617 nm was synthesized through a simple mixing method, in which the carbon quantum dots (CDs) self-assembled with the YVO4 :Eu 3+ nanoparticle, due to the high affinity of oxygen-containing groups such as –COOH or –OH of CDs to the metal ions on the surface of YVO4 :Eu 3+ . The red fluorescence of YVO4 :Eu 3+ @CDs located at 617 nm can be quenched by Cu 2+ ions efficiently, while the blue emission remains invariable; based on this, we construct a ratio fluorescent probe YVO4 :Eu 3+ @CDs for Cu 2+ ion detection, in which the blue emission of CDs is selected as the reference signal, and the red emission of YVO4 :Eu 3+ acts as an output signal. Furthermore, the addition of biothiol recovers the quenched red fluorescence quickly, which can be completed in 18 minutes. Thus, YVO4 :Eu 3+ @CDs can also be used as a 'turn on' ratio fluorescent probe for biothiol rapid detection. Taking l -cysteine (l -Cys) as the model, the fluorescence intensity of the 617 nm peak increases with increasing Cys, and the ratio of F617 /F405 is linear to the concentration of Cys in the range of 0.1 μM to 10 μM with a detection limit of 41 nM. Compared with these single wavelength emission biothiol fluorescent probes, an obvious change in the fluorescence color from blue to pink can be conveniently observed by the naked eye under a UV lamp. Meanwhile, this ratiometric probe has also been demonstrated to be used for the visual identification of biothiols in real blood serum samples.